Learning from the First Step: UniMail, Geneva, Switzerland - McAdam, Daisy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
UniMail, which is the University of Geneva building dedicated to the humanities, is situated in the heart of the city. Students are an integral part of the life of the district with the university situated next to a beautiful landscaped park surrounded by 600 flats. A central lane lets local inhabitants stroll through the main building on to a square, then right into the park.